1994
DOI: 10.1103/physrevb.49.5662
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of (100) diamond surfaces using molecular dynamics with combined quantum and empirical forces

Abstract: Classical trajectory calculations were employed to study diamond (100) surface reconstructions. Atomic forces were computed from two types of potential-energy functions. A quantum mechanical potential based on the semiempirical PM3 (parametric method number three) Hamiltonian was used to describe the central core of the surface model, while an empirically parametrized potential was developed to extend the size of the model surface. The results indicate that the most energetically favorable surface consists of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0

Year Published

1996
1996
2000
2000

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 39 publications
4
34
0
Order By: Relevance
“…Therefore, we obtained normal-mode frequencies by repeating the calculations using smaller clusters, modeled after C 9 H 12 examined in our previous studies, [17][18][19]34 where in most cases all atoms were allowed to relax. The small-cluster calculations were performed using standard MOPAC subroutines.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we obtained normal-mode frequencies by repeating the calculations using smaller clusters, modeled after C 9 H 12 examined in our previous studies, [17][18][19]34 where in most cases all atoms were allowed to relax. The small-cluster calculations were performed using standard MOPAC subroutines.…”
Section: Methodsmentioning
confidence: 99%
“…Zhang et al 15 reported that the dihydride phase is energetically favored over the monohydride phase relative to H desorption, while it is unfavorable with respect to H 2 desorption. On the other hand, earlier studies by Yang et al 16 using a nonself-consistent tight binding model with parameters obtained from density functional theory (DFT), and by Skokov et al 17 using molecular dynamics with a semiempirical Hamiltonian, reported a (3 1):1.33H structure to be most favorable energetically. This structure consists of alternating monohydride carbon dimers and dihydride units.…”
Section: Introductionmentioning
confidence: 98%
“…While calculations of the energetics of surface states [9][10][11][12] can provide the kinetics of individual reaction events, and predictions of surface atomic [13][14][15][16] and electronic [17][18][19] structures are useful in determining the stability of surface atomic configurations, these techniques are inapplicable to the time and length scales required to study diamond film growth. One-dimensional growth models [20][21][22][23] have been useful for verifying proposed growth mechanisms.…”
Section: Introductionmentioning
confidence: 99%